2004
DOI: 10.3354/dao059057
|View full text |Cite
|
Sign up to set email alerts
|

Haemolymph parasite of the shore crab Carcinus maenas: pathology, ultrastructure and observations on crustacean haplosporidians

Abstract: A protozoan parasite with some features of haplosporidians is described from the European shore crab Carcinus maenas. The parasite establishes a systemic infection through the haemal sinuses and connective tissues. Intracellular stages of the parasite were found within reserve inclusion, connective tissue, and muscle cells, while free forms were present in all haemal spaces. A uninucleate stage appeared to develop to a multinucleate plasmodial stage following multiple mitotic divisions of the nucleus. Histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 40 publications
(73 reference statements)
3
24
1
Order By: Relevance
“…Periodic occurrence and dispersal may also pose difficulties in detection. For example, H. littoralis (Figure 1c) is present and monitored in C. maenas in Newton's Cove, yet was not detected in our libraries, possibly due to the fact that transmission stages are not released from infected hosts (Stentiford et al, 2004(Stentiford et al, , 2013 or because two nucleotide mismatches are present between the primers and the H. littoralis sequence. It is a priority for future work to determine to what extent molecular detection of haplosporidian lineages can be associated with actual infections and potential for disease.…”
Section: Phylogenetic Patternsmentioning
confidence: 97%
See 2 more Smart Citations
“…Periodic occurrence and dispersal may also pose difficulties in detection. For example, H. littoralis (Figure 1c) is present and monitored in C. maenas in Newton's Cove, yet was not detected in our libraries, possibly due to the fact that transmission stages are not released from infected hosts (Stentiford et al, 2004(Stentiford et al, , 2013 or because two nucleotide mismatches are present between the primers and the H. littoralis sequence. It is a priority for future work to determine to what extent molecular detection of haplosporidian lineages can be associated with actual infections and potential for disease.…”
Section: Phylogenetic Patternsmentioning
confidence: 97%
“…There are currently four recognised haplosporidian genera: (1) Bonamia: four described species, all economically important oyster parasites in temperate waters; (2) Minchinia: a sparsely recorded genus of five species with sequence data from molluscs from the US Atlantic coast, Western Australia and Europe; (3) Urosporidium: one described species with sequence data (U. crescens; (Flores et al, 1996) and another sequenced specimen (Reece et al, 2004), both occurring as hyperparasites of trematode worms; and (4) Haplosporidium: the most intensively studied and diverse genus (approximately 40 species to date) and perhaps paraphyletic (Burreson and Ford, 2004). Most known members of the genus infect molluscs, but some infect crustaceans (Burreson and Ford, 2004;Stentiford et al, 2004) and annelids (Siddall and Aguado, 2006). A minority of lineages infect freshwater molluscs (Molloy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larsson and Køie (2005) suggested that the inclusion bodies in cell 5 of Paramyxoides spores were haplosporosomes, despite lacking a medul-la, typical of haplosporosomes. They may be haplosporosome-like bodies similar to those in a haplosporidian parasite of Carcinus maenas (see Stentiford et al 2004). Similar structures to those in cell 5 of Paramyxoides nephtys reported by Larsson and Køie (2005) are referred to as "rod-like structures" in cell 4 of Marteilia spp.…”
Section: Discussionmentioning
confidence: 50%
“…Studies indicate that a spot prawn parasite (SPP) in Pandalus spp. (Reece et al 2000, Bower & Meyer 2002, and another protistan from crabs (Carcinus maenas) (Stentiford et al 2004), are also haplosporidians. A molecular study (Reece & Stokes 2003) places the multi-nucleate stage of a haplosporidian of New Zealand abalone (Haliotis iris) parasite (NZAP) , as phylogenetically basal to Urosporidium spp., Haplosporidium spp., Bonamia spp., and Minchinia spp.…”
Section: Introductionmentioning
confidence: 99%